2018
DOI: 10.3892/ol.2018.8971
|View full text |Cite|
|
Sign up to set email alerts
|

miR-185 inhibits cell migration and invasion of hepatocellular carcinoma through CDC42

Abstract: Hepatocellular carcinoma (HCC) is a primary liver cancer with high incidence and mortality. miR-185, a microRNA with appriximately 22-28 nucleotides, was reported to be involved in many cancers. The potential mechanism of miR-185 on HCC through cell division cycle 42 (CDC42) was investigated. RT-qPCR was used to measure the RNA level of miR-185 and CDC42 in HCC tissues and cells. The dual luciferase reporter assay was used to verify whether CDC42 was a target gene for miR-185. Transwell assay was employed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Literature has also recorded that enhanced miR-185 suppressed CRC cancer cell colony formation ability and enhanced apoptosis 29 . A similar study by Zhang et al has reported that miR-185 was downregulated in HCC, and enhancing miR-185 could dampen HCC cell migration and invasion 30 . Anyhow, miR-185 was an-tumor in cancers and its upregulation served to slow down tumor progression.…”
Section: Discussionmentioning
confidence: 58%
“…Literature has also recorded that enhanced miR-185 suppressed CRC cancer cell colony formation ability and enhanced apoptosis 29 . A similar study by Zhang et al has reported that miR-185 was downregulated in HCC, and enhancing miR-185 could dampen HCC cell migration and invasion 30 . Anyhow, miR-185 was an-tumor in cancers and its upregulation served to slow down tumor progression.…”
Section: Discussionmentioning
confidence: 58%
“…In this study, three softwares: TargetScan, miRDB and miRanda were used to predict the target genes for Previous research shown that CDC42 is a potential target of miR-185. For example, Zhang et al [21] confirmed that CDC42 is a direct target of miR-185 in human hepatocellular carcinoma using luciferase reporter assays. Liu et al [28] shown that miR-185 expression significantly suppressed the RhoA and CDC42 3'UTR activities using a luciferase-reporter assay, and could inhibit the proliferation and invasion of human colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we researched the expression profiles of the ileum miRNAs of 7 days piglets infected with Clostridium perfringens type C using small RNA-Seq, and found that ssc-miR-185 was differentially expressed between the resistant groups and susceptibility groups of diarrhea piglets [14]. It is reported that miR-185 can play important roles in a variety of cancers, covering pancreatic cancer [15], bladder cancer [16], non-small cell lung cancer [17], prostate carcinoma [18], gastric cancer [19], breast cancer [20], hepatocellular carcinoma [21] and colorectal cancer [22]. In addition, miR-185 can also play a regulatory role in response the immune inflammatory.…”
Section: Introductionmentioning
confidence: 99%
“…Two additional targets of miR-185 are the Rho GTPases, CDC42 and RHOA ( Table 4 ), implicated in cell cycle, cellular function and maintenance, and cell signaling. By targeting these mRNAs, miR-185 has been shown to inhibit cell proliferation and migration in hepatic, colorectal, and lung cancer cell models [ 45 , 46 , 47 , 48 ]. Importantly, miR-185 can also interact with and target the long noncoding RNA FOXD2-AS1, known to inhibit cell proliferation, migration, and epithelialā€“mesenchymal transition (EMT) in glial cells and renal fibrosis models [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%